Collected writings of Charles Brockden Brown. - Brown, Charles Brockden, 1771-1810 (Collected Writings of Charles Brockden Brown., 2013)
The Letters and Early Epistolary Writings of Charles Brockden Brown gathers and presents, for the first time, the complete extant correspondence of a key American author, along with early manuscript fictions never before published and new scholarly work contextualizing and exploring the writings and their context. The volume is edited to highest scholarly standards and bears the seal of the Modern Language Association's Committee on Scholarly Editions. </sp.